Aortic dissection with left supraclavicular pulsatile swelling: a rare presentation - Khandelwal, Utkarsh; Kashyap, Prashant; Rajpal, Deepali; Shah, Manhar; Baviskar, Ajit; Mathew, Manu (International Journal of Research in Medical Sciences, 2017)
We are presenting a case of aortic dissection with rare presentation. Patient came with complaints of left sided supraclavicular pulsatile swelling and incidentally was recorded with high blood pressure. After series of investigations he was diagnosed as a case of aortic dissection.